Responding to second-tier customers' sustainability expectations through sourcing and procurement - Palosaari, Julia (My University, 2023)
Corporate responsibility is extending beyond company boundaries and home country. The reputation of multinational corporations (MNCs) is at risk due to the increasing number of scandals related to environmental and social responsibility violations. Moreover, MNCs are held liable for possible environmental and social problems of their suppliers. Equally, several scholars recognize the importance of sustainable procurement in sustainable supply chain management where stakeholder collaboration is considered the most effective in addressing issues on climate change. This thesis focuses on the cooperation aspect among multiple stakeholders and, explores how an MNC operating in the manufacturing industry responds to its second-tier customers’ sustainability expectations through sustainable sourcing and procurement. This study aims to address two key research gaps. First, our understanding about sustainability in procurement and supply chain is limited to the first-tier cooperation between different stakeholders such as manufacturer – supplier or manufacturer – customer. This study expands our understanding about sustainable procurement practices by researching the supplier – manufacturer – second-tier customer relationship in the supply chain. Second, although the literature recognizes the role of the first-tier customer in the supply chain as extremely important in shaping the operation of the manufacturer, the role of the second-tier customer is examined less. Therefore, this study focuses on the second-tier customers in the supply chain by illustrating how their sustainability expectations might shape the operations of the manufacturer. To address these research gaps a theoretical framework was established by conducting an extensive literature review focusing on the fields of sustainable development, sustainable supply chain management, and sustainable sourcing and procurement. The research was conducted as a qualitative single case study to UPM Raflatac. To understand how UPM Raflatac responds to its second-tier customers’ sustainability expectations, seven key people working within sourcing and procurement, sustainability and brand owner interface were interviewed. The data were collected and further analyzed through the lenses of interpretivism, allowing to understand how the topic of the research is perceived among professionals working in the field of the research. The results indicate that UPM Raflatac responds effectively to the sustainability expectations of its second-tier customers. According to the findings the sustainability expectations of the second-tier customers focused on four main areas: the use of recycled materials in UPM Raflatac products, recyclability of products, traceability of raw materials used and overall, the availability of high-quality data. Additionally, sustainability is strongly integrated to the business model and UPM Raflatac has processes in place that support creation of a sustainable sourcing and procurement process that can be offered as an example to other companies working in the field.

Yritysvastuu ulottuu yli yritysrajojen ja kotimaan. Monikansallisten yritysten maine on vaarassa ympäristö- ja yhteiskuntavastuu-rikkomuksiin liittyvien skandaalien lisääntymisen vuoksi. Lisäksi monikansalliset yhtiöt ovat vastuussa toimittajiensa mahdollisista ympäristö- ja sosiaalisista ongelmista. Samanaikaisesti useat tutkijat tunnustavat kestävien hankintojen merkityksen kestävässä toimitusketjun hallinnassa, jossa sidosryhmäyhteistyötä pidetään tehokkaimpana ilmastonmuutokseen liittyvien toimien ongelmien ratkaisemisessa. Tämä opinnäytetyö keskittyy useiden sidosryhmien yhteistyöhön ja tutkii, miten teollisuusalalla toimiva monikansallinen yritys vastaa toisen tason asiakkaidensa kestävyysodotuksiin kestävän hankinnan avulla. Tämän tutkimuksen tavoitteena on käsitellä kahta keskeistä tutkimusaukkoa. Ensinnäkin ymmärryksemme hankinnan ja toimitusketjun kestävyydestä rajoittuu ensimmäisen tason yhteistyöhön eri sidosryhmien, kuten valmistajan – toimittajan tai valmistajan – asiakkaan välillä. Tämä tutkimus laajentaa ymmärrystämme kestävistä hankintakäytännöistä tutkimalla toimitusketjun toisen tason asiakassuhdetta. Toiseksi, vaikka kirjallisuudessa tunnustetaan ensimmäisen tason asiakkaan rooli toimitusketjussa erittäin tärkeäksi valmistajan toiminnan muovaamisessa, toisen tason asiakkaan roolia on tutkittu vähemmän. Siksi tässä tutkimuksessa keskitytään toimitusketjun toisen tason asiakkaisiin havainnollistamalla, miten heidän kestävän kehityksen odotuksensa voivat vaikuttaa valmistajan toimintaan. Näiden tutkimusaukkojen korjaamiseksi luotiin teoreettinen kehys tekemällä laaja kirjallisuuskatsaus, joka keskittyi kestävän kehityksen, kestävän toimitusketjun hallinnan sekä kestävän hankinnan aloihin. Tutkimus toteutettiin UPM Raflatacille laadullisena yksittäisenä tapaustutkimuksena. Sen ymmärtämiseksi, miten UPM Raflatac vastaa toisen tason asiakkaidensa vastuullisuus-odotuksiin, haastateltiin seitsemää avainhenkilöä, jotka työskentelevät hankinnan, vastuullisuuden ja brändirajapinnassa. Aineistoa kerättiin ja analysoitiin edelleen selittävän tutkimusfilosofian linssien kautta, jolloin voitiin ymmärtää, miten tutkimusaiheen aihe koetaan tutkimusalalla työskentelevien ammattilaisten keskuudessa. Tulokset osoittavat, että UPM Raflatac vastaa tehokkaasti toisen tason asiakkaidensa vastuullisuus-odotuksiin. Tulosten mukaan toisen tason asiakkaiden vastuullisuusodotukset keskittyivät neljään pääalueeseen: kierrätysmateriaalien käyttöön UPM Raflatac -tuotteissa, tuotteiden kierrätettävyyteen, käytettyjen raaka-aineiden jäljitettävyyteen ja yleisesti korkealaatuisen datan saatavuuteen. Lisäksi vastuullisuus on vahvasti integroitu liiketoimintamalliin ja UPM Raflatacilla on käytössä prosessit, jotka tukevat kestävän hankintaprosessin luomista, jota voidaan tarjota esimerkkinä muille alalla toimiville yrityksille.
Keywords: supply chains; sustainable development; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business